APPLICATION OF EXPERT SYSTEM USING FORWARD CHAINING METHOD FOR WEB-BASED DIAGNOSIS OF CHILD DIARRHEA - Nadia Elmi; Rolly; Ari Dermawan (Informatika, Universitas Jenderal Soedirman, 2022)
Diarrhea is the cause of infant death due to diarrhea which leads to dehydration. Babies who are able to digest solid foods and are experiencing diarrhea should temporarily stay away from oily, high-fiber, sweet foods such as cakes and dairy products. This is because these types of foods can worsen their diarrhea symptoms. Currently, to distinguish the type of diarrhea suffered by children is still limited to conventional diagnosis with pediatricians. it is necessary to build a system on computer applications to help diagnose children's diarrheal diseases so that they can provide information on what types of diarrheal diseases are being experienced for fast and accurate treatment. In the health sector there is an artificial intelligence called an expert system, which is a computer system that uses knowledge, facts and reasoning techniques in solving problems that can usually only be solved by an expert in their field. This research uses the Forward Chaining method where the goal driven data will start searching at the initial node to the goal node until it gets results. The result of the implementation of the system is that the system provides questions in the form of symptoms that must be answered by the patient based on the symptoms experienced by the patient and the results of the process the system will provide information on what type of diarrheal disease the child is experiencing in order to get a solution with treatment.